Research of Pronoun Renjia in Semantic and Rhetorical Function - Sofi Zhang (Humaniora, 2013)
Pronoun renjia is a personal pronoun and its basic functions similar to “other people”. But, in the actual use of pronoun renjia, it can refer to the third person “he, she, they”, refers to the second “you”, and refers to the first person "I, we ". Pronoun renjia has a wide range of functions with a rich function of rhetoric and rhetorical effect compared to the three pronouns. The context of classroom teaching, appropriate design of language environment of pronoun renjia will give student a better understanding on the pronoun renjia’s usage.